STUDENTS’ READINESS IN ADOPTING TECHNOLOGY FOR HISTORY LEARNING IN CENTRAL JAVA - Sariyatun, Sariyatun; Sutimin, Leo Agung; Ardianto, Deny Tri (International Conference On Social Science Education, 2023)
This research aims to portrait students’ readiness for technologized history learning especially in the context of Central Java Indonesia. The qualitative descriptive approach was used as the research method. The subjects of the research were 90 Senior High School students in Central Java, Indonesia. The data collected by interview and questionnaire about the students’ readiness in using technology. The data were analyzed using an interactive analysis. The findings of the research indicate that students have readiness belonging to “good category” for dealing with the utilization of technology in history learning. This positive indication should be perceived as a potent to develop appropriate digital learning material that can be used to support the practices of history learning. This research can provide information to teachers and readers that students are already in a good category in the use of technology. The hope is that all schools can be facilitated by computer laboratories so that students and teachers can easily utilize and integrate technology in history learning. This research can provide information to teachers and readers that students are already in a good category in the use of technology. The hope is that all schools can be facilitated by computer laboratories so that students and teachers can easily utilize and integrate technology in history learning.